APPLICATION OF COMMUNICATION THEORY IN PUBLIC HEALTH CAMPAIGNS - Syarifuddin Syarifuddin; Indah Sulistiani; Laode Aharuddin Kapege; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
This literature review aims to analyze the effectiveness of communication theories in improving public health campaign outcomes. By studying various sources and related literature, the review identifies how the use of communication theories, such as Meaningful Action Theory, Diffusion of Innovations Theory, and Behavior Change Theory, can provide valuable insights in planning and implementing effective communication strategies in a public health context. From this analysis, the study also considered the influence of technology and media in facilitating the dissemination of health messages, as well as how target audiences receive and process these messages. The results show that the strategic application of communication theory has significant potential in improving the effectiveness of public health campaigns. Key findings highlighted the importance of tailored approaches to specific audiences to increase resonance and relevance of messages, the importance of integrating multimedia communication strategies to extend reach and impact, and the need to understand the dynamics and preferences of target audiences. By strategically applying communication theory in the design and implementation of health campaigns, organizations and practitioners can achieve increased awareness, attitude change, and adoption of desired health behaviors among the broader public. The implications of these findings underscore the importance of a theory-based communication approach in enhancing the effectiveness of public health interventions.